Mathematical Foundations of Information Quality Assessment of Oil and Gas Enterprises: Qualimetric Approach - Витвицька, О. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The present article deals with the value aspects of evaluation of oil-and-gas enterprises’ information capital. There was defined the range of the basic qualitative information properties, which have direct impact on the evaluation of the information’s quality as also on the character of managerial decisions making. These properties include: timeliness, topicality, novelty, reliability, relevance, clarity, inconsistency, the degree of accuracy, compliance with applicable regulations and requirements, value, full disclosure, materiality, necessity applicability, relevance of information. The list of components, which form the internal and external micro - and macro information environment of oil-and-gas enterprises functioning, has been selected. To value qualitative properties of information with the help of quantitative indicators, it is proposed to apply the qualimetric model. To implement qualimetrics approach to value information’s assessment, there have been systematized information characteristics, which have direct impact on the quality of the information. On this basis, the tree of qualitative information’s characteristics is constructed. For each characteristic is defined relative indicator of the first level and aggregate indicators of the second level. Numerical characterization of the information’s quality is an integral indicator of the quality of information, which is the result of the convolution and is determined on the basis of the tree of qualitative information’s characteristics, weighting factors and relative performance of all properties.